Regional whole plant and molecular response of Kochia scoparia to glyphosate - Wiersma, Andrew, author; Westra, Philip, advisor; Leach, Jan, advisor; Reddy, Anireddy, committee member; Holtzer, Thomas, committee member (Colorado State University. Libraries, 2012)
Globally, glyphosate (Roundup®) resistant weeds pose a serious challenge to modern agricultural practices that utilize glyphosate for weed control, including Roundup Ready® cropping regimes. Locally, glyphosate resistant Kochia scoparia have been identified throughout the central Great Plains, and the infested range is expanding rapidly. Glyphosate and Roundup Ready® crops form the foundation of no-till technology, which has considerably reduced water use and soil loss in arid to semi-arid regions of North America. Unfortunately, the continued spread of glyphosate-resistant K. scoparia will jeopardize the utility of glyphosate and the sustainability of no-till agricultural practices. In an effort to suppress glyphosate-resistant K. scoparia, more needs to be known about 1) the spread of resistance, 2) the level of resistance, and 3) the mechanism responsible for glyphosate resistance in K. scoparia. Suspected glyphosate-resistant K. scoparia accessions were collected from Kansas, Colorado, North Dakota, South Dakota, and Alberta. Whole plant glyphosate dose response and shikimate assays were used to confirm resistance and assess the level of resistance. Then PCR, quantitative PCR, sequencing, and immunoblotting techniques were used to determine the mechanism responsible for glyphosate resistance. Sequence of the EPSPS binding site proline confirmed that amino acid substitution at that residue was not responsible for resistance in K. scoparia. However, quantitative PCR estimates of EPSPS copy number revealed increased copy number in all glyphosate-resistant individuals —ranging from 3 to 9 EPSPS copies relative to the reference ALS gene. Furthermore, increased EPSPS copy number was correlated to increased transcript and protein abundance. Based on these finding, I confirm resistance for all tested accessions throughout the North American central Great Plains, and conclude that increased glyphosate rates will have little effect in controlling glyphosate-resistant K. scoparia. Furthermore, I suggest that EPSPS gene amplification may be the mechanism responsible for glyphosate resistance in K. scoparia, and that lower level increases in EPSPS expression (as compared to A. palmeri) are sufficient for glyphosate resistance. Moreover, this research, again, demonstrates the adaptability of plants and foreshadows the need for diversifying weed management practices.
Keywords: gene amplification; glyphosate; herbicide; Kochia scoparia; resistance; weed